Effects of tidal periodicities and diurnal foraging constraints on the density of foraging wading birds. (4th May 2016) - Calle, Leonardo; Gawlik, Dale E.; Xie, Zhixiao; Green, Lauri; Lapointe, Brian; Strong, Allan
Abstract: In intertidal zones, tidal cycles reduce water depths and provide areas of shallow water where wading birds can forage for aquatic prey (water depths 0–50 cm). However, a bird that forages diurnally can make use of only a portion of the tidal cycle, which can limit fulfillment of energetic demands. Furthermore, daily and biweekly (spring–neap) tides may compound effects on shallow-water availability for foraging birds. However, the relative effects of daily and biweekly tidal periodicities on the foraging ecology of wading birds are seldom investigated due to a lack of appropriate tools. Therefore, we developed a tidal simulation model to provide dynamic spatiotemporal estimates of the availability of water depths that are within the upper and lower bounds of the birds' foraging water depth limits ("shallow-water availability"). We studied two wading bird species, the Little Blue Heron ( Egretta caerulea ), a daytime-only forager, and the Great White Heron ( Ardea herodias occidentalis ), which feeds both diurnally and nocturnally, to evaluate the relative effects of daily and biweekly tides on shallow-water availability and on patterns in abundance of foraging birds. Seasonal foraging surveys ( n = 38; 2011–2013) were conducted by boat along a 14-km transect adjacent to extensive intertidal flats in the lower Florida Keys, USA. For both species combined, biweekly tides resulted in a 0.61- to 6.09-fold change in abundance, whereas daily tides resulted in a 1.03- to 5.81-fold change in abundance. Diurnal shallow-water availability was not consistently correlated in magnitude or direction with spring–neap tidal cycles because differences in tide height between consecutive low tides were larger than changes in tidal amplitude from spring–neap tide cycles. Thus, the strong response by birds to the spring–neap tide was likely driven by mechanisms other than diurnal shallow-water availability alone.